Pengaruh Strategi Promosi Sosial Media Instagram Terhadap Kepuasan Konsumen di Barbershop Athena - Adi Hardiyansah; Dini Yani; Rieke Retnosary (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to explore the impact of promotion strategies through Instagram social media on customer satisfaction at Athena Barbershop. Involving 342 customer respondents, data was collected through the distribution of questionnaires to assess perceptions of Instagram promotions and the level of satisfaction with the barbershop's services. This research employs a quantitative analysis, specifically simple regression analysis, with data processed using the Statistical Product and Service Solutions (SPSS) software version 27.0. The results of the study indicate that the promotion strategy using Instagram social media has a significant influence on customer satisfaction at Athena Barbershop.